Analysis of the Role of Organizational Culture at the Center for Employee Education and Training - Dedy Achmad, Kurniady (2020)
The purpose of this study was to analyze the role of organizational culture at Bandung Regional Ministry of Education and Training Center. This research was conducted with a descriptive research method with a qualitative approach. The data were collected through interview, observation, and document review. The analysis results showed the following(1) Organizational culture seen from the aspect of providing a sense of identity, a role in an effort to arouse commitment to the organization's mission and its role in clarifying the standard of behavior has not played an optimal role one of them do not use complete attributes and do not use uniforms according to the rules (2) The obstacle in implementing organizational culture at Bandung Regional Ministry of Education and Training Center is that there are still employees who are more concerned with personal interests so that work is often neglected. Many employees are still lazy to follow the flag ceremony. (3) The efforts made by the Bandung Regional Ministry of Education and Training Center to discipline employees by distributing examples of uniformed rules that are correct in accordance with the rules, direct supervisor approach to be able to foster subordinates to work better.